A novel inflammatory pathway mediating rapid hepcidin-independent hypoferremia - Guida, Claudia; Altamura, Sandro; Boutros, Michael; Muckenthaler, Martina (Blood, 2015)
Regulation of iron metabolism and innate immunity are tightly interlinked. The acute phase response to infection and inflammation induces alterations in iron homeostasis that reduce iron supplies to pathogens. The iron hormone hepcidin is activated by such stimuli causing degradation of the iron exporter ferroportin and reduced iron release from macrophages, suggesting that hepcidin is the crucial effector of inflammatory hypoferremia. Here, we report the discovery of an acute inflammatory condition that is mediated by Toll-like receptors 2 and 6 (TLR2 and TLR6) and which induces hypoferremia in mice injected with TLR ligands. Stimulation of TLR2/TLR6 triggers profound decreases in ferroportin messenger RNA and protein expression in bone marrow-derived macrophages, liver, and spleen of mice without changing hepcidin expression. Furthermore, C326S ferroportin mutant mice with a disrupted hepcidin/ferroportin regulatory circuitry respond to injection of the TLR2/6 ligands FSL1 or PAM3CSK4 by ferroportin downregulation and a reduction of serum iron levels. Our findings challenge the prevailing role of hepcidin in hypoferremia and suggest that rapid hepcidin-independent ferroportin downregulation in the major sites of iron recycling may represent a first-line response to restrict iron access for numerous pathogens.
Gesehen am 19.12.2018